THE INFLUENCE OF TEACHER PERCEPTIONS OF PRINCIPAL LEADERSHIP AND TEACHER WORK MOTIVATION ON TEACHER PERFORMANCE (SURVEY AT SOUTH JAKARTA PRIVATE VOCATIONAL SCHOOLS) - Maman Darmansyah; Didi Sujadi (Jurnal Scientia, 2023)
The Influence of Teacher Perceptions of Principal Leadership and Teacher Work Motivation on Teacher Performance (Survey at South Jakarta Private Vocational Schools). If there really is a positive and significant relationship, then how strong is the relationship between Teacher Perceptions of Principal Leadership and Teacher Work Motivation and Teacher Performance. The research method used is a survey with correlation and regression analysis, namely connecting data showing Teacher Perceptions of Principal Leadership and Work Motivation with data showing Teacher Performance. Data regarding Teacher Perceptions of Principal Leadership, Teacher Work Motivation on Teacher Performance was obtained through a questionnaire compiled by researchers, namely measuring things related to the three things above: There is a significant influence on teacher perception of the principal's leadership style and teacher work motivation together on teacher performance. This can be proven by the value of F0 = 54.476 and sig 0.000 < 0.05. There is a significant influence of perceptions of the principal's leadership style on teacher performance. This can be proven by the value t0 = 6.924 and sig 0.000 < 0.05. There is a significant influence of teacher work motivation on teacher performance, which is not significant. This can be proven by the value t0 = 5.846 and sig 0.000 > 0.05.